Exposure to family and domestic violence is associated with increased childhood hospitalisations. - Carol Orr; Colleen M Fisher; David B Preen; Rebecca A Glauert; Melissa O'Donnell (PLoS ONE, 2020)
Background Children's exposure to family and domestic violence (FDV) is a global public health concern and is considered one of the most common and severe stressors children can experience. While it is acknowledged that children who are exposed to FDV have poorer general health, there is a lack of data on the outcomes of children exposed to FDV. The use of longitudinal data has been suggested as a way to gain an understanding of the impact on children's long-term outcomes. Methods Our cohort study used deidentified individual-level linked administrative data of children born 1987-2010, in Western Australia, who were exposed to FDV in the prenatal period (12 months prior to birth) to five years of age (early years). Results Children exposed to FDV are more likely to be hospitalised than non-exposed children. Children exposed to FDV in both the prenatal and early childhood period had a threefold increased odds of mental health hospitalisation. We found a significant increase in odds of pregnancy-related hospitalisation in FDV exposed children. When stratified by Aboriginal status, Aboriginal children had a higher proportion of hospitalisations than non-Aboriginal children. Conclusion Exposed children have an increased likelihood for hospitalisation than non-exposed children. Within the exposed cohort differences were apparent between Aboriginal and non-Aboriginal children. Aboriginal children had greater odds for hospitalisation in most of the diagnostic groups compared to their non-Aboriginal counterparts. Our findings represent an important advance in the literature with respect to the burden of disease of children exposed to FDV.